Identification of antifungal compounds from slender amaranth - Akbar,Muhammad (2020)
Abstract Background: Antifungal activity of slender amaranth (Amaranthus viridis L.) is well documented but such studies are scarce in Pakistan, especially against plant pathogens. It was hypothesized that A. viridis has antifungal activity against fungal phyto-pathogens also. Objective: Identification of antifungal constituents from leaf extracts of A. viridis. Methods: Different organic solvent extracts of A. viridis leaves were evaluated against 5 plant pathogenic fungal species viz. Alternaria alternata, Aspergillus flavus, Drechslera australiensis, Fusarium oxysporum and Macrophomina phaseolina. Antifungal activity of A. viridis was determined by serial dilution method. Six levels (0, 5, 10, 15, 20 and 25 mg mL-1) of treatments of each n-hexane, chloroform and ethyl acetate were employed against all fungal species in a Completely Randomised Design (CRD). Results: Generally, all organic solvent extracts reduced the fungal biomass significantly with the increase in extract concentration but ethyl acetate leaf fraction exhibited pronounced activity and reduced the fungal growth up to 44% in A. alternata, 39% in A. flavus, 48% in D. australiensis, 48% in F. oxysporum and 45% in M. phaseolina. Gas Chromatography Mass Spectrometry (GCMS) analysis of ethyl acetate leaf fraction revealed 09 compounds. Out of these 9 compounds, one compound identified as 1,2- Benzenedicarboxylic acid, mono (2-ethylhexyl) ester) showed 58.5% peak value. Conclusions: It was concluded that 1,2- Benzenedicarboxylic acid, mono (2-ethylhexyl) ester) being in the highest concentration in the ethyl acetate leaf fraction of A. viridis may be responsible for antifungal activity. This compound can serve as structural analog to develop ecofriendly fungicides.